The role of banks in monitoring firms : the case of the Crédit Mobilier - Paulet, Elisabeth, 1962- (Routledge explorations in economic history., 1999)
This book is a timely examination of banks and corporate finance. It addresses such issues as credit constraints, the supervisions of managers and the stabilization of share prices.